Analytic hierarchy process‐based prioritization framework for vendor's reliability challenges in global software development. Issue 3 (19th August 2020) - Khan, Abdul Wahid; Hussain, Imtiaz; Zamir, Muhammad
Abstract: The concept of global software development was adopted by software organizations for the purpose of delivering quality software products at a reduced cost. Software reliability became one of the eminent challenges in the global software development. The main objective of this research paper is to develop a classification of the challenging factors in the global software development process faced by vendor organizations. The classification of the challenges depends on the data gathered through systematic literature review and implementation of the analytic hierarchy process (AHP). A total of 18 challenges were explored through systematic literature review and mapped into five categories, that is, capability, reliance, delivery, management, and distinction. The explored issues played a major role for assisting the researcher and designer for mitigating the challenges during "AHP based prioritization framework for Vendor's Reliability challenges in Global Software Development". Taking the AHP approach, we tried to fill this research gap by exploring and prioritizing the challenges that could negatively impact the vendor reliability of a specific organization. The classification of the explored challenges provided a framework that was used to deal with the issues associated with software reliability in the global software environment, which provided the vital role for the success of software organizations.